Clinical Proficiency of Low Hemoglobin Density and Microcyte Anemia Factor Parameters for the Diagnosis of Functional Iron Deficiency from Absolute Iron Deficiency in Chronic Inflammation - Fatemeh Karamshahi; Ali Noori-Zadeh; Ali Seidkhani-Nahal; Abdollah Davodian; Gholam Basati; Iraj Alipourfard (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Inflammatory conditions affect iron status due to inflammation-induced changes in acute-phase proteins. However, distinguishing between functional and absolute iron deficiency severity can aid early treatment, necessitating the exploration of cost-effective laboratory tests for early iron deficiency treatment. Thus, the aim of this study was to evaluate the clinical efficacy of new tests in this area, including %LHD (Low Hemoglobin Density%) and Maf (Microcyte Anemia Factor). Materials & Methods: This study was conducted on 130 individuals with chronic inflammation (C-reactive protein positive) and serum iron levels below the reference range, with a mean age of 49.5 years. Iron and total iron-binding capacity (TIBC) were measured by photometric and magnesium carbonate precipitation methods, respectively. Ferritin was measured by ELISA, CRP by latex hemagglutination, and complete blood count (CBC), along with two new red blood cell parameters, %LHD and Maf, which were calculated using a cell counter and mathematical formulas. For statistical analyses, SPSS V.27 and MedCalc V.22 were used at a significance less than 0.05. Results: Out of 130 patients, 62.3% had Functional Iron Deficiency (FID) and 37.7% had Absolute Iron Deficiency (AID). FID patients had significantly higher mean values of Fe, Hb, Hct, MCH, MCHC, MCV, TSAT, RBC, and Maf compared to AID patients. Maf showed 97% clinical sensitivity and 86% specificity for diagnosing functional iron deficiency versus absolute iron deficiency, while %LHD had lower sensitivity and specificity. Conclusion: Among the new red blood cell parameters, although both %LHD and Maf can be used to differentiate patients with absolute iron deficiency from those with functional iron deficiency, Maf demonstrated higher clinical sensitivity and specificity.